Platelet rich plasma in treatment of chronic non healing ulcers: a study of ten cases - Deshmukh, Nitika S.; Belgaumkar, Vasudha A.; Tolat, Sunil N.; Chavan, R. B.; Vamja, Chirag J. (International Journal of Research in Dermatology, 2018)
Background: Platelet rich plasma (PRP) helps tissue re-modulation by its growth factors (GFs)– platelet derived growth factor (PDGF), transforming growth factor (TGF-β), epidermal growth factor (EGF), fibroblast growth factor (FGF-2), insulin-like growth factor (IGF). These GFs aid healing by attracting undifferentiated stem cells into newly formed matrix and triggering cell division; by promoting capillary growth and by attracting macrophages to improve tissue healing and regeneration. The aims and objectives of the study were to assess reduction in wound size of chronic non-healing ulcers by autologous platelet rich plasma and to evaluate the safety of autologous platelet rich plasma in treatment of chronic non healing ulcers. Methods: This was an experimental study conducted on ten patients of chronic non-healing ulcers of varied etiology. Autologous PRP was freshly prepared using 10 ml of patient’s own blood by differential centrifugation process and injected at the margins and base of each ulcer. Four such sittings were administered at weekly intervals for four weeks with a post-treatment follow-up period of one month. Total duration of our study was 8 weeks. Objective assessment of ulcer size was done using centimetre scale and documented by digital photographs. Results: While 40% of chronic ulcers healed completely, the remaining 60% cases showed signs of healing at the end of 8 weeks. Mean improvement in ulcer size was 69.38% over a period of 8 weeks. No side effect was encountered in any of our cases. Conclusions: Platelet rich plasma hastened the healing process of chronic non-healing ulcers. Being autologous, it has rare chances of hypersensitivity reactions.